Semiotic Analysis of Bullying Practices in Drama School 2015: Study of Emile Durkheim's Theory of Suicide - Khanifah, Anisatul; Harianto, Sugeng (Universitas Muhammadiyah Surakarta, 2024)
The existence of humans as social beings is represented through the formation of social groups as an effort to maintain and develop their lives. However, instead of forming harmony and balance, humans also often commit social deviations, one of which is through bullying behavior. Bullying behavior does not only occur in the work environment but has entered the school environment. One of them is in South Korea, where bullying rates and suicide rates are both high, showing that there is a relevance between bullying rates and suicide rates. Now, this phenomenon is constructed through drama as a reflection of social reality. The focus of this research is to find out how the practice and relevance of bullying behavior and suicide cases in the 2015 school drama. The research method used is Ferdinand De Saussure's semiotic analysis method which focuses on discussing the concept of signifiers and signifieds. The data studied are pieces of dialogue, images, and sound. In this study the authors used Emile Durkheim's Suicide theory. The findings in this study are that there is a relevance between bullying practices and suicide cases. This is also exacerbated by the finding that victims of bullying often do not have adequate social groups. Because the more individuals have sufficient social groups, then this is capital in maintaining their lives from other social groups. The location of the social group greatly influences a person's decision to commit suicide. Thus, the social group has an important position for a person as part of his efforts to defend himself and maintain his self-esteem and the harmony of social relations.